2005
DOI: 10.1073/pnas.0505210102
|View full text |Cite
|
Sign up to set email alerts
|

Control over brain activation and pain learned by using real-time functional MRI

Abstract: If an individual can learn to directly control activation of localized regions within the brain, this approach might provide control over the neurophysiological mechanisms that mediate behavior and cognition and could potentially provide a different route for treating disease. Control over the endogenous pain modulatory system is a particularly important target because it could enable a unique mechanism for clinical control over pain. Here, we found that by using real-time functional MRI (rtfMRI) to guide trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
611
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(648 citation statements)
references
References 39 publications
20
611
3
8
Order By: Relevance
“…One of the early and most notable rtfMRI-nf studies implemented a careful design and reported robust findings that subsequently sparked considerable enthusiasm (deCharms et al, 2005). This study demonstrated that individuals who suffered from chronic pain and received veritable rtfMRI-nf learned to modulate neural activity in the rostral ACC.…”
Section: Fmrimentioning
confidence: 77%
See 1 more Smart Citation
“…One of the early and most notable rtfMRI-nf studies implemented a careful design and reported robust findings that subsequently sparked considerable enthusiasm (deCharms et al, 2005). This study demonstrated that individuals who suffered from chronic pain and received veritable rtfMRI-nf learned to modulate neural activity in the rostral ACC.…”
Section: Fmrimentioning
confidence: 77%
“…Likewise, multiple experiments train down-regulation of the ACC to mitigate pain (deCharms et al, 2005;Guan et al, 2015) or inhibit cigarette cravings (Canterberry et al, 2013;Li et al, 2012), while others encourage ACC activity to heighten valence ratings (Gröne et al, 2015) or limit the effects of cognitive interference (Mathiak et al, 2010). Thus, researchers are already training regulation in opposite directions, but shy away from directly comparing the behavioral effects of up-versus down-regulation using a specific pattern of brain activity.…”
Section: Future Stepsmentioning
confidence: 99%
“…In addition to its excellent spatial resolution and its non-invasive nature, real-time (rtfMRI) or near real-time processing of fMRI data [Cox et al, 1995;Yoo et al, 1999] has provided a means for individuals to receive information relating to the state of their own brain activity [Posse et al, 2003;Weiskopf et al, 2003]. For example, fMRI was applied for the regulation of painrelated activity in rostral-ventral/dorsal parts of the anterior cingulate cortex [deCharms et al, 2005]. Posse et al [2003] studied the feasibility of inducing human emotion by measuring the MR signal changes associated with amygdala activation.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, continued advances in MR imaging systems and experimental sophistication with blood oxygenation level dependent (BOLD) [Ogawa et al, 1990a,b] imaging have led to the emergence of real-time fMRI as a viable tool for real-time biofeedback [deCharms et al, 2004[deCharms et al, , 2005Posse et al, 2003;Weiskopf et al, 2003;Yoo et al, 2004;Yoo and Jolesz, 2002]. The most recent work of deCharms et al [2005] represents a particularly compelling example of the utility of real-time fMRI for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%